Body Adiposity Changes After Lifestyle Interventions in Children/Adolescents and the NYD-SP18 and TMEM18 Variants - Zlatohlavek, Lukas; Maratka, Vit; Tumova, Eva; Ceska, Richard; Lanska, Vera; Vrablik, Michal; Hubacek, Jaroslav A (Medical Science Monitor, 2018)
BACKGROUND This study was carried out to determine the relationship between the common TMEM-18 (rs4854344, G>T) and NYD-SP18 (rs6971091, G>A) gene variants and weight loss after lifestyle interventions (increased physical activity in conjunction with optimal dietary intake) in overweight/obese children/adolescents. MATERIAL AND METHODS We genotyped 684 unrelated, white, non-diabetic children (age 12.7±2.1 years, average BMI at baseline 30.66±4.80 kg/m²). Anthropometric and biochemical examinations were performed before and after 4 weeks of an intensive lifestyle intervention. RESULTS The mean weight loss achieved was 5.20±2.02 kg (P<0.001). NYDSP-18 AA homozygotes had significantly higher abdominal skinfold value before and after the intervention (both, P=0.001). No significant associations between BMI decrease and the NYD-SP18 and TMEM18 variants were found. Associations between all anthropometrical and biochemical changes and genes remained non-significant after data were adjusted for sex, age, and baseline values. CONCLUSIONS Decreased body weight in overweight/obese children is not significantly influenced by the NYD-SP18 rs6971091 or TMEM18 rs4854344 polymorphisms.
Keywords: obezita; Membrane Proteins; Polymorphism, Single Nucleotide; hmotnostní úbytek; Humans; index tělesné hmotnosti; Body Mass Index; Overweight; dítě; Child; jednonukleotidový polymorfismus; Female; jaderné proteiny; Genotype; lidé; Adiposity; ženské pohlaví; Life Style; Male; životní styl; Weight Loss; Adolescent; Nuclear Proteins; membránové proteiny; genotyp; Obesity; Body Weight; Exercise; tělesná hmotnost; mužské pohlaví; cvičení; adipozita; nadváha; mladiství